The Influence of Card Sort Learning Media on Stuidents’ Learning Outcomes in Subtheme 1 How Clean Air Processes by Body in Grade V UPTD SDN 122337 Pematang Siantar - Rosiana Hutabalian; Lisbet Novianti Sihombing; Desi Sijabat (MultiTech Publisher, 2023)
This research aims to determine whether there is an influence of Card Sort Learning Media on student learning outcomes in theme 2, sub-theme 1, how the body processes clean air. In class V UPTD SD Negeri 122337 Pematang Siantar, the method in this research is a quantitative method, experimental type, which takes the form of a research design. is a pre-experimental type one group pretest-posttest. Conducted in October 2023, the population of all students at UPTD SD Negeri 12 2337 Pematang Siantar and the sample used was a saturated sample of 30 student. The variant used is two research variables: dependent variable (x) learning media and Card Sort (y) student learning outcomes , data collection techniques, namely test techniques with validity tests, reliability tests, difficulty level tests, and distinguishing power tests. Test results using the Normality test, Homogeneity test and the N-gain technique with the help of the SPSS version 21 program, based on the calculation results obtained the l homogeneity l ni l bag test by using the l Le l ve l ne l di l pe test l role l h ni l lai l si l gni l fi l kan sel l be l sar 0.097 yai l tu le l bi l h be l sar of l t table l l 0.05. So it is also with the results of l l ni l lai l pre l te l st which me l m l li l ki l average 46.33 while on the results of l l postte l st ni l la l the average is 82.83 ni l la lai l pe l rbandi l ngan or to l nai l kan from l ni l lai l pre l te l st to l postte l st yai l u 36% While the results of the l l test l N-Gai l n me l mpe l role l h ni l la l Me l an 0.76 then if l ka di l li l hat of l ti The level of gni l fi l can be grouped into categories of categories l e l fe l kti l f . So it can be concluded that there is an influence on the use of media in the Card Sort learning lesson on the learning outcomes of self - employed students on topic 2 , subsection 1 to l las V di l UPTD SD Ne l ge l ri l 12237 Pe l ripe Si l inter.